FruHis significantly increases the anti-benign prostatic hyperplasia effect of lycopene: A double-blinded randomized controlled clinical trial - Sadeghi, Alireza; Saedisomeolia, Ahmad; Jalili-Baleh, Leili; Khoobi, Mehdi; Soleimani, Mohammad; Fakhr Yasseri, Ali Mohammad; Yekaninejad, Mir Saeed; Farzin, Amirreza; Amini, Erfan; Nowroozi, Mohammad Reza (Frontiers in Nutrition, 2022)
Background: For decades, lycopene was considered as main compound of tomato protecting benign prostatic hyperplasia (BPH). Recent animal studies suggest that a newly discovered compound “FruHis” boosts lycopene for its action. This study aimed to determine whether FruHis enhances the action of lycopene to modify the laboratory parameters and clinical outcomes of patients with BPH. Methods: Current study was conducted on 52 BPH patients, who were randomly assigned into four groups of treatments: lycopene plus FruHis (n=11, 25 mg/day lycopene and 10 mg/day FruHis), lycopene (n=12, 25 mg/day lycopene), FruHis (n=12, 10 mg/day FruHis) and placebo (n=13). Patients received these supplements for 8 weeks. Results: FruHis intake strengthened the reducing effects of lycopene on insulin-like growth factor-1 (IGF-1) (-54.47 ± 28.36 ng/mL in the lycopene + FruHis group vs. -30.24 ± 46.69 ng/mL in the lycopene group), total prostate-specific antigen (TPSA) (-1.49 ± 4.78 ng/mL in the lycopene + FruHis group vs. (-0.64 ± 2.02 ng/mL in the lycopene group), and symptom score (-4.45 ± 4.03 in the lycopene + FruHis group vs. -1.66 ± 5.41 in the lycopene group) in BPH patients. Such findings were also seen for body mass index (BMI) and waist circumference (WC). However, except for IGF-1, these reductions were not statistically significant compared with the placebo, and the intakes of lycopene and FruHis alone, however, were clinically important. Such effects of lycopene and FruHis were not seen for free PSA (FPSA) and FPSA/TPSA ratio. Conclusion: Despite the non-significant effects of lycopene and FruHis, it seems that FruHis intake strengthens the beneficial effects of lycopene on IGF-1, TPSA, and symptom score among BPH patients. This study was registered in the www.irct.ir (reference: IRCT20190522043669N1).